Outcome Analysis of Clinical Evaluation and Surgical Management of Different Grades of Gynecomastia - Ahmad AbdElhady Muhammad Ibrahim; Samia Mohammed Ahmed Saied; Mohammed Ahmed Omar; Ahmed Ali Abdelrahim Ali (SVU - International Journal of Medical Sciences)
Background: : Gynecomastia (GM) is the most common breast condition in males. The clinical evaluation and surgical management of different grades of Gynecomastia are described extensively throughout several previous literatures. Objectives: The objective of our present study is to assess the epidemiological, clinical presentation, and the preferred type of surgical intervention along with evaluation of aesthetic outcomes of each procedure. Patients and methods: This is a prospective descriptive case series study conducted on 30 patients who was presenting with different grades of true gynecomastia admitted to the Plastic Surgery department in Qena university hospital from the outpatient clinic and seeking surgical correction. Results: Fifty eight breasts were operated upon in 30 patients; two cases (6.67%) had unilateral Gynecomastia and 28 cases (93.33%) had bilateral lesion.Based on surgical intervention, periareolar excision was performed in ten cases, liposuction was performed in six cases, periareolar excision combined with liposuction was done in 4 cases. While, circumareolar excision combined with liposuction was performed in two cases and, circumareolar concentric mastopexy without liposuction was performed in four cases. Four cases of grade III gynecomastia were treated with free nipple grafts. Conclusion: Gynecomastia is a persistent growth of breast tissue in men and the most successful course of management is surgery. Liposuction and surgical resection and/or combined procedures are three main types for surgical alternatives.